Identification of the Material Phases Location for the One-Dimensional Unsteady Heat Conduction Problem - Korycki, R. (Engineering Transactions, 2000)
The present paper is devoted to identification of the material phases location for one-dimensional structure with respect to the first-order sensitivity of the identification functional. A transient heat conduction problem within a thermal anisotropic one-dimensional structure is formulated. The material derivative concept and both the direct and adjoint approaches are used in considering the shape identification of the problem domain. The identification functional is assumed in the form of the "distance" between the temperature of the identified body and the measured temperature of real structure. Stationarity conditions are formulated with respect to the obtained first-order sensitivities. Numerical examples of internal boundary identification are presented.